Organizational Planning and Business Human Resource Management: A Systematic Qualitative Review - Dyah Ayu Dwi Kusumaningrum; Agung Winarno (CV. Lenggogeni Data Publishing, 2024)
Sustainability in accomplishing organizational objectives is highly dependent on HRM and organizational planning. Organizations confront more complicated problems in today's corporate world because of globalization, sustainability demands, and fast technological progress. In today's business world, effective organizational planning and human resource management techniques are critical for companies to stay competitive and adaptable. This systematic qualitative evaluation aims to examine different methods and practices in human resource management and organizational planning by reviewing a large body of literature. The major goals of this review are to (1) identify current trends, (2) assess the advantages and disadvantages of these trends and solutions, and (3) assess the effect of these tactics on the performance of businesses across different industries. This review sheds light on the relationship between organizational sustainability, HRM practices, and strategic planning by synthesizing and analyzing pertinent papers using a rigorous and open methodology. The results of this review provide scholars and practitioners with actionable advice to improve the efficiency and longevity of organizations.